2018
DOI: 10.1159/000487818
|View full text |Cite
|
Sign up to set email alerts
|

The Understanding and Management of Organism Toxicity in Septic Shock

Abstract: The toxicity caused by different organisms in septic shock is substantially complex and characterized by an intricate pathogenicity that involves several systems and pathways. Immune cells’ pattern recognition receptors initiate the host response to pathogens after the recognition of pathogen-associated molecular patterns. In essence, the subsequent activation of downstream pathways may progress to infection resolution or to a dysregulated host response that represents the hallmark of organ injury in septic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Despite the fact that the relationship between PCSK9 and intestinal permeability has not been studied in depth, it is known that LDL-R is implicated in LPS clearance [11]. Moreover, previous studies have shown that the inhibition of PCSK9 and the consequent promotion of LDL-R favor LPS detoxification [27][28][29], indicating PCSK9 as a possible regulator of LPS clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that the relationship between PCSK9 and intestinal permeability has not been studied in depth, it is known that LDL-R is implicated in LPS clearance [11]. Moreover, previous studies have shown that the inhibition of PCSK9 and the consequent promotion of LDL-R favor LPS detoxification [27][28][29], indicating PCSK9 as a possible regulator of LPS clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Ooi et al [10] observed that individuals with PCSK9-LOF had lower postprandial triglyceridemia, apoB-48, and total apoB levels, consistent with the results observed in vitro and in rodents. On the other hand, it has been observed that PCSK9 inhibition is implicated in the clearance of pathogen lipids, such as lipopolysaccharide (LPS), through LDL receptor (LDLR) [11,12] while Grin et al [13] reported that high concentrations of PCSK9 directly suppress uptake of lipopolysaccharide by hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…During the late phase of sepsis and in septic shock, there are numerous hemodynamic, microcirculatory, cellular, and metabolic abnormalities that cause increased mortality and morbidity in affected patients ( 50 ). In general terms, the most important circulatory damage leading to multi-organ dysfunction is induced in part by the activation of the complement cascade and impairment in both platelets and neutrophils, including the excessive production of NETs ( 51 ). Dysregulated activation of the complement cascade, which is a tightly regulated multiprotein complex and a major component of the innate immune response, is designed to detect, destroy, and clear invading pathogens as well as amplifying the inflammatory response ( 52 ).…”
Section: Pathophysiology Of Sepsismentioning
confidence: 99%
“…In this issue of the Journal of Innate Immunity, Siemens et al [7] characterize a novel virulence factor of group B streptococci, i.e., a pigment toxin that caused the release of proinflammatory cytokines and induced blood clotting on the bacterial cell surface. In a clinical setting, the cytotoxic properties indeed play important roles in the clinical picture [8]. In another interesting article, Tsai et al [9] show that when exposing macrophages to group B streptococci, sialic acid-binding immunoglobulin-type lectin receptors (Siglecs) modulate the response, where Siglec-14 had an enhancing effect whereas Siglec-5 reduced inflammasome activation and macrophage IL-1β release.…”
mentioning
confidence: 99%